Atrazine exposed phytoplankton causes the production of non-viable offspring on Daphnia magna. (March 2019) - Religia, Pijar; Kato, Yasuhiko; Fukushima, Ery Odette; Matsuura, Tomoaki; Muranaka, Toshiya; Watanabe, Hajime
Abstract: This study focuses on the possibility that herbicide-exposed phytoplankton will cause sub-lethal effect on zooplankton. Atrazine, phytoplankton Raphidocelis subcapitata and zooplankton Daphnia magna were chosen as a model chemical and organisms. R. subcapitata was exposed to atrazine at 150 μg/L, harvested and fed to D. magna . While the mothers fed with atrazine-exposed phytoplankton did not show any abnormalities, they produced non-viable offspring. Number of non-viable offspring at the first clutch was high but the number was reduced at later stages and viable offspring was produced. This result indicates that phytoplankton exposed to sub-lethal dose of atrazine affects population dynamics of its predator, D. magna. Highlights: Daphnia fed with atrazine exposed algae produces non-viable juveniles. Adverse effect of atrazine exposed algae is severer than direct atrazine exposure. Number of non-viable juveniles decreases in later clutches. Atrazine incorporated to Daphnia may be transferred to the eggs or detoxified during maturation of mother.